2021
DOI: 10.1080/0960085x.2020.1869508
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad, and the ugly: impact of analytics and artificial intelligence-enabled personal information collection on privacy and participation in ridesharing

Abstract: Big data analytics (BDA) and artificial intelligence (AI) may provide both bright and dark sides that may affect user participation in ridesharing. We do not know whether the juxtaposed sides of these IT artifacts influence users' cognitive appraisals, and if so, to what extent will their participative behavior be affected. This paper contributes to the IS research by uncovering the interplay between the dark and bright sides of BDA and AI and the underlying mechanisms of cognitive appraisals for user behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 71 publications
0
42
1
3
Order By: Relevance
“…Lentzsch et al (2021) have shown that malicious users can pressure innocent users unintendedly to reveal information after downloading seemingly harmless data onto the PVA they are using. Inability to administer and change privacy as well as content settings for AI-based technologies leads to mistrust, which emphasizes the importance of designing PVAs to be highly privacy-sensitive and trustworthy (Cheng et al, 2021;Cho et al, 2020).…”
Section: Drawbacks Of Using Ai-based Technologiesmentioning
confidence: 99%
“…Lentzsch et al (2021) have shown that malicious users can pressure innocent users unintendedly to reveal information after downloading seemingly harmless data onto the PVA they are using. Inability to administer and change privacy as well as content settings for AI-based technologies leads to mistrust, which emphasizes the importance of designing PVAs to be highly privacy-sensitive and trustworthy (Cheng et al, 2021;Cho et al, 2020).…”
Section: Drawbacks Of Using Ai-based Technologiesmentioning
confidence: 99%
“…It thus represents a black box for humans that prevents understanding certain decisions and leads to increased uncertainty (Venkatesh, 2021). In the context of generating predictions involving humans, this negatively affects the privacy perceptions of individuals (Cheng et al, 2021). While there are arguments that highlight the bright side of AI, such as improvements to efficiency or cost reduction, aspects of the dark side of AI may have a stronger effect on the perceptions of employees toward AI (Grundner & Neuhofer, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, AI might lead to value co-destruction when discrepancies between users emerge (Camilleri & Neuhofer, 2017). Furthermore, the use of AI could also support the development of uncertainty and invasion of privacy (Cheng et al, 2021). This negative phenomenon is often referred to as the dark side of AI, referring to how AI presents risks for individuals, organizations, and society (Alt, 2018;Grundner & Neuhofer, 2021;Wirtz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Customers' experience-based human-computer interactions(HCIs)enhances customers' abilities to participate in value creation and inspires customers to participate in value co-creation. The value co-creation participation behavior of customers in the case, based on the Cloud Warehouse system platform, has obvious ITenabled value co-creation, and therefore, the dimensions of customer participation in value co-creation are divided into informational participation, actionable participation, and attitudinal participation [54,55]. Moreover, IT enablement dimensions are divided into structural enablement and resource enablement regarding digital enablement dimensions [35].…”
Section: Supply Chain Flatteningmentioning
confidence: 99%